A carbon negative electrode material, a battery negative electrode sheet, a battery and a preparation method thereof

Through the carbonization method after vacuum pre-carbonization and impregnation treatment, carbon anode material with a high pore ratio was prepared, which solved the problem of insufficient energy storage performance of the battery and significantly improved the reversible capacity and cycling performance of the battery.

CN118929624BActive Publication Date: 2025-04-11GUANGDONG DINA NEW MATERIAL TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410984636.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-04-11
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

In the existing electrochemical energy storage technology, the electrode material performance of lithium-ion batteries and sodium-ion batteries is insufficient, which affects the energy storage performance of the battery.

Method used

After vacuum pre-carbonization and impregnation in the impregnation liquid, carbonization is performed to prepare a carbon negative electrode material with a larger pore size and a high pore ratio.

Benefits of technology

The closed-cell size and proportion of hard carbon materials are significantly increased, and the reversible capacity and cycling performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118929624B_ABST
    Figure CN118929624B_ABST
Patent Text Reader

Abstract

The present application proposes a carbon negative electrode material, a battery negative electrode sheet, a battery and a preparation method thereof. The negative electrode material is prepared by the following preparation method: a precursor is vacuum pre-carbonized and impregnated, and then carbonized to obtain the carbon negative electrode material; volatile substances such as organic matter contained in the precursor are fully removed by vacuum pre-carbonization; a substance decomposed at high temperature is used as an impregnation liquid to decompose and volatilize during the carbonization process, thereby increasing the number of pores and pore volume of the hard carbon material; thereby achieving a higher reversible capacity of the carbon negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of electrochemical energy storage technology, and in particular relates to a carbon negative electrode material, a battery negative electrode sheet, a battery and a preparation method thereof. Background Art

[0002] The renewable clean energy currently being developed and used, such as wind energy, solar energy, tidal energy, etc., are all intermittent energy, and the generation and supply of energy are discontinuous or unstable. If these intermittent and unstable electric energies are incorporated into the power grid, it will seriously interfere with the normal operation of the power grid. Therefore, the development of new energy storage technologies that meet the requirements of "low cost", "high safety" and "large scale" for large-scale energy storage applications has become a research hotspot worldwide.

[0003] At present, the main energy storage technologies include electrochemical energy storage, mechanical energy storage, electromagnetic energy storage and phase change energy storage. Compared with other energy storage methods, electrochemical energy storage technology has the characteristics of high efficiency, low investment, safe use and flexible application, which is most in line with the development direction of today's energy. In the field of electrochemical energy storage, lithium-ion batteries and sodium-ion batteries have become the leaders in the field of electrochemical energy storage due to their advantages such as high energy density, environmental friendliness and long service life. The performance of the electrode materials of lithium-ion batteries and sodium-ion batteries has a certain influence on the energy storage performance of the battery. Summary of the invention

[0004] The present application provides a carbon negative electrode material, a battery negative electrode sheet, a battery and a preparation method thereof to solve the problems existing in the related art. The technical solution is as follows:

[0005] In a first aspect, the present invention provides a carbon negative electrode material and a method for preparing the same, comprising the following steps:

[0006] The precursor is carbonized after vacuum pre-carbonization and impregnation to obtain the carbon negative electrode material; the vacuum pre-carbonization conditions are: vacuum degree <-0.08Mpa, 200-900°C for 1-20h;

[0007] The impregnation process is: the vacuum pre-carbonized material is immersed in an impregnation liquid for treatment;

[0008] The impregnation liquid is a solution containing one or a combination of two or more of PMMA, ammonium bicarbonate, ammonium binitrate, ammonium nitrate, ammonium sulfate, and ammonium bisulfate.

[0009] In one embodiment, the vacuum pre-carbonization further includes a crushing process; after the crushing process, carbonization is performed.

[0010] In one embodiment, the precursor is one or a combination of two or more of wheat, rice, wheat bran, rice bran, wood, bamboo, asphalt, tar or smokeless carbon.

[0011] In one embodiment, the pulverizing process is: pulverizing by using a jet mill, a sand mill, a roll mill or a ball mill.

[0012] In one embodiment, the D50 of the material after the pulverization process is 2-10 um.

[0013] In one embodiment, the impregnation process is as follows: the concentration of the impregnation solution is 0.1-1 mol / L; and the impregnation time is 15-60 min.

[0014] In one embodiment, the carbonization condition is 900-1700° C. for 2-50 h.

[0015] In one embodiment, the carbonization process is carried out in two steps;

[0016] The first step is to treat at 900-1500°C under vacuum conditions for 1-49h;

[0017] The second step is to treat at 1000-1700° C. for 1-49 hours under a protective gas atmosphere; the protective gas is one of argon, nitrogen or hydrogen or a mixture of two or more.

[0018] In a second aspect, an embodiment of the present application provides a carbon negative electrode material, which is prepared by the above-mentioned method for preparing a carbon negative electrode material.

[0019] In a third aspect, an embodiment of the present application provides a battery negative electrode sheet, comprising the carbon negative electrode material described above.

[0020] In a fourth aspect, an embodiment of the present application provides a battery, wherein the battery is a lithium-ion battery or a sodium-ion battery, and the lithium-ion battery or the sodium-ion battery includes the negative electrode sheet described above.

[0021] The advantages or beneficial effects of the above technical solution include at least:

[0022] 1. A method for preparing a carbon negative electrode material of the present application, wherein the precursor is subjected to vacuum pre-carbonization and impregnation in an impregnation liquid, and then subjected to carbonization treatment to prepare a carbon negative electrode material. The vacuum pre-carbonization of the present application can solidify the precursor and remove volatile substances such as organic matter contained in the precursor; during the impregnation process, the space left by removing the volatile substances can allow the impregnation liquid to enter the material; in the subsequent carbonization process, the impregnation liquid in the material volatilizes and decomposes at high temperature, which can increase the number of pores and pore volume of the material; the carbonization process causes the carbon atom layer to bend at high temperature, and multiple carbon layers are bent and overlapped to form a closed-pore hard carbon material; therefore, the preparation method of the present application can increase the size and proportion of closed pores in the hard carbon material, and achieve a higher reversible capacity.

[0023] 2. A carbon negative electrode material, a battery negative electrode sheet and a battery of the present application. The carbon negative electrode material of the present application is obtained by the preparation method of the present application, and has a larger pore size and a higher pore ratio; it is used as a battery negative electrode sheet and assembled into a lithium-ion battery or a sodium-ion battery, and the battery has a higher reversible capacity and cycle performance.

[0024] The above summary is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments and features described above, further aspects, embodiments and features of the present application will be readily apparent by reference to the accompanying drawings and the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the multiple drawings represent the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings only depict some embodiments disclosed in the present application and should not be regarded as limiting the scope of the present application.

[0026] Figure 1 This is a scanning electron microscope image of the negative electrode material prepared in Example 2 of the present application;

[0027] Figure 2 The adsorption curve diagram of the negative electrode material prepared in Example 2 and Comparative Example 4 of the present application;

[0028] Figure 3 The pore size distribution curves of the negative electrode materials prepared in Example 2 and Comparative Example 3 of the present application;

[0029] Figure 4 The charge and discharge curves of the lithium-ion batteries of Example 2 and Comparative Example 7 of the present application are shown;

[0030] Figure 5 This is the charge and discharge curve of the sodium ion battery of Example 6 of the present application;

[0031] Figure 6 This is the cycle performance curve of the sodium ion battery of Example 6 of the present application;

[0032] Figure 7 The charge and discharge curve of the lithium-ion battery of Example 5 of the present application;

[0033] Figure 8 This is the cycle performance curve of the lithium-ion battery of Example 5 of the present application. DETAILED DESCRIPTION

[0034] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present application. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.

[0035] In the prior art, when preparing hard carbon materials, the precursor is generally pretreated in an inert gas atmosphere, then vacuum pre-carbonized, and finally carbonized to obtain the hard carbon material. However, this process of pre-treatment followed by vacuum treatment is only to deposit the precursor into tar on the surface of the hard carbon material to achieve the effect of coating the hard carbon, and it cannot improve the pores inside the hard carbon material. Therefore, the present application provides a new method for preparing hard carbon as a negative electrode material, which can increase the size and proportion of closed pores in the hard carbon material, and does not require coating to achieve closed pores.

[0036] The present invention provides a carbon negative electrode material and a method for preparing the same, comprising the following steps:

[0037] The precursor is carbonized after vacuum pre-carbonization and impregnation to obtain the carbon negative electrode material; the vacuum pre-carbonization conditions are: vacuum degree <-0.08Mpa, 200-900°C for 1-20h;

[0038] The impregnation process is: the vacuum pre-carbonized material is immersed in an impregnation liquid for treatment;

[0039] The impregnation liquid is a solution containing one or a combination of two or more of PMMA, ammonium bicarbonate, ammonium binitrate, ammonium nitrate, ammonium sulfate, and ammonium bisulfate.

[0040] In one embodiment, the impregnation liquid is a DMF solution containing PMMA; or the impregnation liquid is an aqueous solution containing one or a combination of two or more of ammonium bicarbonate, ammonium binitrate, ammonium nitrate, ammonium sulfate, and ammonium bisulfate.

[0041] In the present application, pre-carbonization is carried out at 200-900°C for 1-20h; the internal structure of the precursor material can be solidified, and organic matter with a low decomposition temperature in the raw material can be removed; the treatment is carried out at a vacuum degree of <-0.08Mpa, and all volatile substances in the precursor material can be extracted under a vacuum state. On the one hand, the removal of volatile substances forms an internal space inside the precursor material; on the other hand, the removal of volatile substances can prevent the carbonization of volatile substances during subsequent carbonization, thereby clogging the internal space of the closed pores of the hard carbon material.

[0042] In one embodiment, the pre-carbonization temperature is 300-700° C., and the treatment time is 2-15 hours.

[0043] The solute in the impregnation solution is an organic substance or an inorganic salt; in this embodiment, both the organic substance and the inorganic salt are materials that have no carbon residue after high-temperature decomposition. Preferably, the organic substance is PMMA (polymethyl methacrylate); the inorganic salt is one or a combination of two or more of ammonium bicarbonate, ammonium hydrogen nitrate, ammonium nitrate, ammonium sulfate or ammonium hydrogen sulfate.

[0044] The material after vacuum pre-carbonization in the present application is impregnated into an impregnation liquid. During the vacuum pretreatment process, the removal of volatile substances forms an internal space inside the precursor material, and the internal space and the pores of the material itself can accommodate more impregnation liquid during the impregnation process. The impregnation liquid uses a material with no carbon residue after high-temperature decomposition, which makes it possible to further widen the pore volume and increase the pores during the subsequent carbonization process, and at the same time, no residue will not occupy the volume of the formed pores.

[0045] In one embodiment, the vacuum pre-carbonization further includes a crushing process; after the crushing process, carbonization is performed.

[0046] The main purpose of the pulverization process is to prepare materials of suitable particle size for subsequent carbonization and battery preparation. At the same time, the pulverized particles can better contact with the impregnation liquid during the impregnation process, increasing the penetration of the impregnation liquid.

[0047] In one embodiment, the pulverization method includes, but is not limited to, air jet milling, sand milling, roll milling and ball milling.

[0048] In one embodiment, the particle size D50 of the material after the pulverization treatment is 2 to 10 um. Preferably, the pulverization is performed by jet milling and sand milling, and the particle size of the material after the pulverization is 4 to 8 um.

[0049] In one embodiment, the precursor is one or a combination of two or more of wheat, rice, wheat bran, rice bran, wood, bamboo, asphalt, tar or smokeless carbon.

[0050] The precursor materials are biomass materials or petrochemical derivatives, which are light in source and low in cost.

[0051] In one embodiment, the impregnation process is as follows: the concentration of the impregnation solution is 0.1-1 mol / L; and the impregnation time is 15-60 min.

[0052] In one embodiment, the carbonization condition is 900-1700° C. for 2-50 hours. Carbonization of the material can bend the carbon atom layer in the crushed precursor after high temperature treatment, and multiple carbon layers are bent and overlapped to form closed pores, using its own carbon layer structure without the need for additional coating.

[0053] In one embodiment, the carbonization process is carried out in two steps;

[0054] The first step is to treat at 900-1500°C under vacuum conditions for 1-49h;

[0055] The second step is to treat at 1000-1700° C. for 1-49 hours under a protective gas atmosphere; the protective gas is one of argon, nitrogen or hydrogen or a mixture of two or more.

[0056] The carbonization of the present application is divided into two steps. The first step is carried out under vacuum. Under vacuum, the decomposition substances in the material impregnated with the impregnation liquid during the impregnation process are decomposed at high temperature. Under vacuum, they can be volatilized and removed faster and more fully, which will not affect the overall process of carbonization. The second step of carbonization is carried out under protective gas. In this embodiment, the protective gas is an inert gas such as nitrogen or argon; or the protective gas is a reducing gas such as hydrogen; or it is a mixed gas of an inert gas and a reducing gas, and the reducing gas does not exceed 10% in the mixed gas. The carbonization of the material can bend the carbon atom layer in the crushed precursor after high-temperature treatment, and multiple carbon layers are bent and overlapped to form closed pores. The vacuum pre-carbonization in the previous step of the present application has removed as much material as possible that may fill the closed pore space. Therefore, the closed pore space of the hard carbon material obtained by carbonization is larger, and a higher reversible capacity can be achieved.

[0057] The embodiment of the present application also provides a carbon negative electrode material, which is prepared by the above-mentioned method for preparing a carbon negative electrode material.

[0058] An embodiment of the present application also provides a battery negative electrode sheet, comprising the carbon negative electrode material described above.

[0059] An embodiment of the present application further provides a battery, wherein the battery is a lithium ion battery or a sodium ion battery, and the lithium ion battery or the sodium ion battery comprises the negative electrode sheet described above.

[0060] In this embodiment, the reversible capacity of the sodium battery reaches 449 mAh / g, and the capacity of the lithium-ion battery can reach 350 mAh / g.

[0061] The following is a further description with reference to specific embodiments.

[0062] Example 1

[0063] This example provides a method for preparing a carbon negative electrode material, which is as follows:

[0064] Put 50g of rice bran into a tube furnace and treat it at 500℃ for 12h under vacuum; put the pre-carbonized product into a sand mill and sand grind it for 3h to reduce the material particle size D50 to 5um; put the pre-carbonized balls into a 0.5mol / L ammonium bisulfate solution and immerse them for 30min, centrifuge and filter them for later use; take 5g of the impregnated material, put it into a tube furnace, treat it at 900℃ for 20h under vacuum, switch to nitrogen atmosphere, treat it at 1300℃ for 2h, and cool it to obtain the carbon negative electrode material. Example 2

[0065] This example provides a method for preparing a carbon negative electrode material, which is as follows:

[0066] Put 100g of corn into a tubular furnace and treat it at 400℃ for 6h under vacuum; put the pre-carbonized product into a sand mill and sand grind it for 5h, and the material particle size D50 is reduced to 3um; put the pre-carbon balls into a 5g / L PMMA solution and immerse them for 60min, centrifuge and filter them for later use; take 5g of the impregnated material, put it into a tubular furnace, treat it at 1000℃ for 18h under vacuum, switch to nitrogen atmosphere, treat it at 1200℃ for 4h, and cool to obtain the carbon negative electrode material.

[0067] Example 3

[0068] This example provides a method for preparing a carbon negative electrode material, which is as follows:

[0069] Put 100g of asphalt into a tubular furnace and treat it at 900℃ for 1h under vacuum; put the pre-carbonized product into a sand mill and sand grind it for 3h, and the material particle size D50 is reduced to 7um; put the pre-carbon balls into 0.5mol / L ammonium sulfate solution and immerse them for 30min, centrifuge and filter them for later use; take 5g of the impregnated material, put it into a tubular furnace, treat it at 1200℃ for 30h under vacuum, switch to argon atmosphere, treat it at 1400℃ for 6h, and cool to obtain the carbon negative electrode material.

[0070] Example 4

[0071] This example provides a method for preparing a carbon negative electrode material, which is as follows:

[0072] Put 100g of bamboo into a tubular furnace and treat it at 200℃ for 20h under vacuum; put the pre-carbonized product into a jet mill for jet crushing, and reduce the material particle size D50 to 6um; put the pre-carbon balls into a 1mol / L ammonium sulfate solution and immerse them for 30min, centrifuge and filter them for later use; take 5g of the impregnated material, put it into a tubular furnace, treat it at 1500℃ for 30h under vacuum, switch to argon atmosphere, and treat it at 1700℃ for 2h; cool it to obtain the carbon negative electrode material.

[0073] Comparative Example 1

[0074] This example provides a method for preparing a carbon negative electrode material, which is as follows:

[0075] Put 100g of corn into a tubular furnace and treat it at 400℃ for 6h in a nitrogen atmosphere; put the pre-carbonized product into a sand mill and sand grind it for 5h, and the material particle size D50 is reduced to 3um; put the pre-carbon balls into a 5g / L PMMA solution and immerse them for 60min, centrifuge and filter them for later use; take 5g of the impregnated material, put it into a tubular furnace, treat it at 1000℃ for 18h in a vacuum environment, switch to a nitrogen atmosphere, treat it at 1200℃ for 4h, and cool it to obtain the carbon negative electrode material.

[0076] Comparative Example 2

[0077] This example provides a method for preparing a carbon negative electrode material, which is as follows:

[0078] Put 100g of corn into a tubular furnace and treat it at 400℃ for 6h in a vacuum atmosphere; put the pre-carbonized product into a sand mill and sand grind it for 5h, and the material particle size D50 is reduced to 3um; put 5g of the pre-carbon ball material into a tubular furnace and treat it at 1000℃ for 18h in a vacuum environment, then switch to a nitrogen atmosphere and treat it at 1200℃ for 4h, and cool to obtain the carbon negative electrode material.

[0079] Comparative Example 3

[0080] This example provides a method for preparing a carbon negative electrode material, which is as follows:

[0081] Put 100g of corn into a tubular furnace and treat it at 400℃ for 6h in a vacuum atmosphere; put the pre-carbonized product into a 5g / L PMMA solution and immerse it for 60min, centrifuge and filter it for later use; take 5g of the impregnated material, put it into a tubular furnace, treat it at 1000℃ for 18h in a vacuum environment, switch to a nitrogen atmosphere, treat it at 1200℃ for 4h, and cool it to obtain the carbon negative electrode material.

[0082] Comparative Example 4

[0083] This example provides a method for preparing a carbon negative electrode material, which is as follows:

[0084] Put 100g of corn into a tubular furnace and treat it at 400℃ for 6h in a nitrogen atmosphere; put the pre-carbonized product into a sand mill and sand grind it for 5h, and the material particle size D50 is reduced to 3um; put 5g of the pre-carbon ball material into a tubular furnace, treat it at 1000℃ for 18h in a vacuum environment, switch to a nitrogen atmosphere, treat it at 1200℃ for 4h, and cool to obtain the carbon negative electrode material.

[0085] The carbon negative electrode material of Example 2 was observed by scanning electron microscope. Figure 1 is a scanning electron microscope image of the negative carbon material of Example 2; Figure 1 It can be seen that the particle size of the material is mainly distributed in the range of 1 to 7 um.

[0086] The carbon negative materials of Example 2 and Comparative Example 4 were subjected to BET test, and their adsorption curves are as follows: Figure 2 As shown, the aperture comparison is Figure 3 As shown. Figure 2 It can be seen that in Example 2 of the present application, the specific surface area of ​​the negative electrode material after carbonization can reach 55 cm 3 g -1 The specific surface area of ​​the negative electrode material of Comparative Example 4 without the above treatment is only 5 cm 3 g -1 Through the method of the present application, the specific surface area is increased by more than 11 times.

[0087] Similarly, the specific surface area of ​​Comparative Example 1 is 27 cm 3 g -1 The specific surface area of ​​comparative example 2 is 13 cm 3 g -1 The specific surface area of ​​comparative example 3 is 44 cm 3 g -1 This indicates that the impregnation of the present invention can significantly increase the pore ratio, and the vacuum pretreatment has a good additive effect on the impregnation.

[0088] Figure 3 In the figure, the test curve is integrated, and the closed area corresponding to the curve represents the number of pores under the diameter. Obviously, the number of pores after vacuum pre-carbonization and impregnation treatment in Example 2 is greater than the number of pores of the negative electrode material without treatment in Comparative Example 4. This indicates that the vacuum pre-carbonization and impregnation treatment of the present application significantly increases the number of pores and specific surface area.

[0089] Example 5

[0090] The hard carbon material obtained in Example 2 is used as the negative electrode active material, and a lithium sheet, a polyethylene separator, and lithium hexafluorophosphate are used as electrolyte salt to prepare a non-aqueous electrolyte lithium ion half-cell; the specific steps are as follows:

[0091] The hard carbon material, PVDF and conductive carbon black are uniformly mixed in a ratio of 90:5:5, and fully mixed with NMP to form a slurry. The above slurry is coated on a copper foil and dried for use; the coated electrode is cut into discs with a diameter of 12 mm, and 2032 type batteries are assembled. The selected lithium sheet is 15.8 (diameter) * 0.45 (thickness) mm, the diaphragm is a 12um thick PE diaphragm, the electrolyte is 1 mol / L lithium hexafluorophosphate electrolyte, and the solvent composition EC:EMC:DMC=1:1:1.

[0092] Example 6

[0093] The difference from Example 5 is that the hard carbon material obtained in Example 2 is used as the negative electrode active material, and a non-aqueous electrolyte sodium ion half-cell is prepared with sodium flakes and sodium hexafluorophosphate as electrolyte salt.

[0094] Comparative Example 4

[0095] The difference between Comparative Example 4 and Example 5 is that the hard carbon material of Comparative Example 1 is used as the negative electrode active material.

[0096] Comparative Example 5

[0097] The difference between Comparative Example 5 and Example 5 is that the hard carbon material of Comparative Example 2 is used as the negative electrode active material.

[0098] Comparative Example 6

[0099] The difference between Comparative Example 6 and Example 5 is that the hard carbon material of Comparative Example 3 is used as the negative electrode active material.

[0100] Comparative Example 7

[0101] The difference between Comparative Example 7 and Example 5 is that the hard carbon material of Comparative Example 4 is used as the negative electrode active material.

[0102] Performance Test:

[0103] The non-aqueous electrolyte ion half-cells of Example 5, Example 6 and Comparative Examples 4-7 were subjected to charge and discharge tests in the voltage range of 0 to 2.0 V. The charge and discharge curves of Example 5 and Comparative Example 7 are shown in FIG. Figure 4 The charge and discharge curves and cycle performance curves of Example 5 are shown in Figure 7-8 The charge and discharge curves and cycle performance curves of Example 6 are shown in Figure 5-6 The first charge capacity is shown in Table 1.

[0104] Table 1 Capacity data of the batteries of Example 5, Example 6 and Comparative Examples 4-7

[0105] Reversible capacity / mAh / g Example 5 342 Example 6 449 Comparative Example 4 314 Comparative Example 5 289 Comparative Example 6 331 Comparative Example 7 245

[0106] pass Figure 4-8 As can be seen from the data in Table 1, the non-aqueous electrolyte ion half-cell was charged and discharged in the voltage range of 0 to 2.0 V. In the lithium ion full cell of Example 5, the carbon negative electrode material of Example 2 was used, and the reversible capacity could reach 342 mAh / g, and the cycle was stable for 200 cycles. In the sodium ion full cell of Example 6, the carbon negative electrode material of Example 2 was used, and the reversible capacity could reach 449 mAh / g.

[0107] In the lithium-ion battery of Comparative Example 4, the carbon negative electrode material of Comparative Example 1 was pretreated in a nitrogen atmosphere. In the nitrogen atmosphere, due to the saturated vapor pressure of the volatile products, the volatiles could not be removed in time, and there would be residues inside the material, resulting in a decrease in the number and volume of closed pores, affecting the reversible capacity of the battery. Therefore, the reversible capacity decreased relative to Example 5, which was 314 mAh / g. The lithium-ion battery of Comparative Example 5 uses the carbon negative electrode material of Comparative Example 2, which has only undergone vacuum pretreatment and no impregnation treatment. The number and volume of pores have not been further improved, so the reversible capacity of the battery is only 289 mAh / g. The lithium-ion battery of Comparative Example 6 uses the carbon negative electrode material of Comparative Example 3. The pretreated carbon material is not ground into small particles. During the impregnation process, it is difficult for the impregnation liquid to impregnate into the interior of the carbon material, which reduces the increase in the number of pores and the expansion of the pore volume during the carbonization process. Therefore, the reversible capacity of the battery is slightly reduced relative to Example 5, which is 331 mAh / g. The lithium battery of Comparative Example 7 uses the carbon negative electrode material of Comparative Example 4, which has neither vacuum pretreatment nor impregnation treatment, so the number and volume of closed pores are poor, which is reflected in the reversible capacity of the battery of only 245 mAh / g, which is much smaller than that of the lithium ion battery of Example 5. Therefore, it can be known that by increasing the closed pore size and proportion of the hard carbon material through the method of the present application, the reversible capacity of the corresponding battery is significantly improved.

[0108] In summary, when preparing the hard carbon negative electrode material in the present application, the precursor is vacuum pre-carbonized and impregnated before being carbonized, which significantly increases the closed pore size and proportion of the hard carbon material, thereby improving the capacity of the battery.

[0109] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory.

[0110] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0111] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a carbon negative electrode material, characterized in that: The following steps are involved: The precursor is treated at a vacuum degree of <-0.08Mpa and 200-900°C for 1-20h for vacuum pre-carbonization; After the crushing treatment, the vacuum pre-carbonized material is immersed in an impregnation liquid for treatment; carbonization is performed to obtain the carbon negative electrode material; The carbonization process is carried out in two steps; The first step is to treat at 900-1500°C under vacuum conditions for 1-49h; The second step is to treat at 1000-1700℃ for 1-49h under a protective gas atmosphere; The impregnation liquid is a solution containing one or a combination of two or more of PMMA, ammonium sulfate and ammonium hydrogen sulfate.

2. The method for preparing a carbon negative electrode material according to claim 1, characterized in that: The precursor is one or a combination of two or more of wheat, rice, corn, wheat bran, rice bran, wood, bamboo, asphalt, tar or smokeless carbon.

3. The method for preparing a carbon negative electrode material according to claim 2, characterized in that: The crushing process is as follows: Use jet mill, sand mill, roller mill or ball mill for crushing; the D50 of the material after crushing is 2~10um.

4. The method for preparing a carbon negative electrode material according to claim 1, characterized in that: The impregnation process is as follows: the concentration of the impregnation solution is 0.1-1 mol / L; the impregnation time is 15-60 minutes.

5. The method for preparing a carbon negative electrode material according to claim 1, characterized in that: The protective gas is one or a mixture of two or more of argon, nitrogen or hydrogen.

6. A carbon negative electrode material, characterized in that: The carbon negative electrode material is prepared by the method for preparing the carbon negative electrode material according to any one of claims 1 to 5.

7. A battery negative electrode sheet, characterized in that: Including the carbon negative electrode material as described in claim 6.

8. A battery, characterized in that: The battery is a lithium ion battery or a sodium ion battery, and the lithium ion battery or the sodium ion battery comprises the battery negative electrode sheet according to claim 7.

Citation Information

Patent Citations

  • Preparation method of porous hard carbon negative electrode material of sodium-ion battery

    CN116986578A

  • Preparation method of composite hard carbon material, composite hard carbon material and application of composite hard carbon material

    CN118343742A

  • Manufacturing method of negative electrode material for nonaqueous electrolyte secondary battery

    JP2008124034A